A rare new treefrog of the genus Sarcohyla (Anura: Hylidae) from Guerrero, Mexico - Grünwald, Christoph I.; Franz-Chávez, Hector; Morales-Flores, Karen I.; Ahumada-Carrillo, Ivan T.; Jones, Jason M. (Zootaxa, 2019)
Based on morphological data collected from treefrogs related to Sarcohyla hazelae, we describe a new species of the genus Sarcohyla from the cloud forest of the Sierra Madre del Sur of Guerrero, Mexico. We compare physical charactersitics of this new species to its closest relatives within the genus Sarcohyla, including dorsal and ventral coloration, head shape, tympanum distinctiveness, morphometrics and the condition of the tubercles on hands and feet. We analyze accoustic data from the advertisement call of males of the new species. We discuss the relationship of the species described herein with several of its cogeners, plus we resurrect the Sarcohyla hazelae group for these frogs. We describe habitat and distribution species related to Sarcohyla hazelae and also comment on the conservation priorities of these frogs.